Improving the Geological Understanding of the Niger Delta Basin of Nigeria Using Airborne Gravity Data - P. O, Eke; F.N, Okeke; P.O, Ezema (International Journal of Geography and Geology, 2016)
Airborne gravity anomaly over parts of Niger delta basin of Nigeria has been interpreted qualitatively and quantitatively. The residual anomaly was obtained from the observed field data through a second order polynomial method and then enhanced by a filtering process. The qualitative interpretation of the gridded data reveals NS, EW and NE-SW trending subsurface structures. The inverse and forward modeling results show spherical and dyke-like anomaly structures at depths of between 1,090 m to 3,538 m, while the density contrast of formations identifies areas of possible hydrocarbon occupation. The Euler deconvolution windowed solutions reveal depth to anomalous sources of between 2,000 m to 9,300 m for structural index of one, and depths of between 3,200 m to 10,600 m for structural index of two. The source parameter imaging reveals depth ranges of between 1,700 m to 10,600 m. The work reveals that the maximum depth to basement in the study area is 10,600 m.